A meta-analysis on the efficacy of tranexamic acid in the treatment of melasma - ALHEJAIRI Rehab; MOHAMMED Abaker Ahmed Alnour Ruaa; ALA'A Suwait Deeb Al Suwait; CHEN Yongfeng (Pifu-xingbing zhenliaoxue zazhi, 2025)
The aim of this study was to compare the efficacy of TXA with other therapies for melasma. Melasma is a common acquired skin condition characterized by hypermelanosis, causing light to dark patches, and is the most prevalent in individuals with Fitzpatrick skin types Ⅲ to Ⅵ. It is a complex condition with an unclear etiology, often influenced by factors such as excessive sun exposure and hormonal changes. Treating melasma poses significant challenges for healthcare providers, primarily due to its tendency to reoccur. This makes management strategies crucial for achieving lasting results and improving patient outcomes. A systematic review of randomized controlled trials (RCTs) was conducted using databases such as MEDLINE, EMBASE, Google Scholar, and Cochrane, yielding 10 studies encompassing 455 participants. The analysis incorporated oral, topical, and injectable forms of TXA, with treatment durations ranging from 8 weeks to 1 year. Pooled results using a random-effects model indicated a moderate effect size of 0.477, suggesting TXA's efficacy in reducing melasma severity. However, high heterogeneity (I2=97.62%) reflected variations in study protocols, TXA delivery methods, and patient demographics.